Therapy-induced senescence contributes to the efficacy of abemaciclib in patients with dedifferentiated liposarcoma - Gleason, Caroline E. (2024)
Purpose: We conducted research on CDK4/6 inhibitors (CDK4/6i) simultaneously in the preclinical and clinical spaces to gain a deeper understanding of how senescence influences tumor growth in humans. Patients and Methods: We coordinated a first-in-kind phase II clinical trial of the CDK4/6i abemaciclib for patients with progressive dedifferentiated liposarcoma (DDLS) with cellular studies interrogating the molecular basis of geroconversion. Results: Thirty patients with progressing DDLS enrolled and were treated with 200 mg of abemaciclib twice daily. The median progression-free survival was 33 weeks at the time of the data lock, with 23 of 30 progression-free at 12 weeks (76.7%, two-sided 95% CI, 57.7%-90.1%). No new safety signals were identified. Concurrent preclinical work in liposarcoma cell lines identified ANGPTL4 as a necessary late regulator of geroconversion, the pathway from reversible cell-cycle exit to a stably arrested inflammation provoking senescent cell. Using this insight, we were able to identify patients in which abemaciclib induced tumor cell senescence. Senescence correlated with increased leukocyte infiltration, primarily CD4-positive cells, within a month of therapy. However, those individuals with both senescence and increased TILs were also more likely to acquire resistance later in therapy. These suggest that combining senolytics with abemaciclib in a subset of patients may improve the duration of response. Conclusions: Abemaciclib was well tolerated and showed promising activity inDDLS. The discovery ofANGPTL4 as a late regulator of geroconversion helped to define how CDK4/6i-induced cellular senescence modulates the immune tumor microenvironment and contributes to both positive and negative clinical outcomes.